Palmitoylethanolamide attenuates neurodevelopmental delay and early hippocampal damage following perinatal asphyxia in rats - Herrera, Maria I.; Udovin, Lucas D.; Kobiec, Tamara; Toro-Urrego, Nicolas; Kusnier, Carlos F.; Kölliker-Frers, Rodolfo A.; Luaces, Juan P.; Otero-Losada, Matilde; Capani, Francisco (Frontiers in Behavioral Neuroscience, 2022)
Impaired gas exchange close to labor causes perinatal asphyxia (PA), a neurodevelopmental impairment factor. Palmitoylethanolamide (PEA) proved neuroprotective in experimental brain injury and neurodegeneration models. This study aimed to evaluate PEA effects on the immature-brain, i.e., early neuroprotection by PEA in an experimental PA paradigm. Newborn rats were placed in a 37° C water bath for 19 minutes to induce PA. PEA 10 mg/kg, s.c., was administered within the first hour of life. Neurobehavioral responses were assessed from postnatal day 1 (P1) to postnatal day 21 (P21), recording the day of appearance of several reflexes and neurological signs. Hippocampal CA1 area ultrastructure was examined using electron microscopy. Microtubule-associated protein-2 (MAP-2), phosphorylated high and medium molecular weight neurofilaments (pNF H/M), and glial fibrillary acidic protein (GFAP) were assessed using immunohistochemistry and Western Blot at P21. Over the first 3 weeks of life, PA rats showed late gait, negative geotaxis and eye-opening onset, and delayed appearance of air-righting, auditory startle, sensory eyelid, forelimb placing, and grasp reflexes. On P21, the hippocampal CA1 area showed signs of neuronal degeneration and MAP-2 deficit. PEA treatment reduced PA-induced hippocampal damage and normalized the time of appearance of gait, air-righting, placing, and grasp reflexes. The outcome of this study might prove useful in designing intervention strategies to reduce early neurodevelopmental delay following PA.